(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
We propose a fractional spline method for solving fractional differential equations subject to initial conditions. Using the Caputo fractional integral and derivative have to construct the spline interpolation with polynomial coefficients. For the given spline function, error bounds were studied and a stability analysis was completed. The numerical explanation for the provided method was considered using three examples. The results show that the fractional spline function which interpolates data is productive and profitable in solving unique problems.